Association between subclinical hyperthyroidism and a PRKAR1A gene variant in Carney complex patients: A case report and systematic review - Wang, Hongyang; Mao, Min; Liu, Dongfang; Duan, Lian (Frontiers in Endocrinology, 2022)
Background and Objectives: It is currently controversial whether subclinical hyperthyroidism is associated with PRKAR1A gene variants. We describe a man with subclinical hyperthyroidism and a PRKAR1A gene variant who was diagnosed with Carney complex (CNC), and we performed a systematic review of published studies to assess the association between PRKAR1A gene variants and the risk of subclinical hyperthyroidism. Design and Methods: The PubMed, EMBASE, OVID, Science Direct, and gray literature electronic databases were searched for articles published from January 2002 to May 2021 using predefined keywords and inclusion and exclusion criteria. Data on thyroid function from selected studies were extracted and analyzed. Results: We identified a CNC patient with a subclinical hyperthyroidism phenotype combined with multiple components and genetic sequenced data. In a subsequent systematic review, twenty selected studies (14 case studies and 6 series studies) enrolling 23 individuals were included in the final analysis. The patient’s thyroid function data were qualitative in 11 cases and quantitative in 12 cases. The prevalence of subclinical hyperthyroidism in the CNC patients with a PRKAR1A gene variant, including our patient, was markedly higher than that in the normal population (12.5% vs. 2%) Conclusions: The findings of this systematic review provide helpful evidence that PRKAR1A gene variants and subclinical hyperthyroidism are related and suggest that subclinical hyperthyroidism may be a neglected phenotype of PRKAR1A gene variants and a novel component of CNC patients.